Study on Cloud Computing Architecture for Telecom Operators - Wei Li; Jihan Li; Yunyong Zhang; Fang Wang (Dianxin kexue)
Definition and characters of c1oud computing were presented.A1so the service architecture and techno1ogy architecture of c1oud computing for te1ecom operators were suggested in detai1.